Comparison of the Structure of Apartments Sold in Two Cities in Northwest Poland - Foryś, Iwona; Batóg, Barbara (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2017)
When evaluating a property, an appraiser should find a real estate market that is similar to the market the evaluated property is on. While similar markets will sometimes not be found in the same city, demographic and economic ratios can be used as criterion of similarity. The analysis and comparison of the structures of apartments sold on two housing markets could also help in confirming the similarity of markets. The similarity of markets could be used in further analyses and property evaluations.The aim of the research is to compare the structures of apartments sold in cities according to the apartments’ attributes, including date of transaction, price, area and location in the city. The housing markets in Szczecin and Bydgoszcz are compared. These cities have a similar number of transactions on their housing markets and have populations of similar size. The data come from notarial deeds for transactions on the secondary housing markets in Szczecin and Bydgoszcz. The analysis is done for two years: 2009, the first year of crisis on the real estate market, and 2015, the year with the most recent data. Measures of entropy and the similarities of the structures are applied.